2018
DOI: 10.1098/rsos.180279
|View full text |Cite
|
Sign up to set email alerts
|

A convenient and eco-friendly cerium(III) chloride-catalysed synthesis of methoxime derivatives of aromatic aldehydes and ketones

Abstract: The use of CeCl3·7H2O as an efficient and eco-friendly promoter for the convenient synthesis of methoximes derived from aromatic aldehydes and ketones, is reported. The transformations entail the use of equimolar amounts of MeONH2·HCl and NaOAc in EtOH at 50°C, and no special precautions are needed with regard to the presence of oxygen. The scope and limitations of the transformation were studied and a reaction mechanism was proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…However, we were inclined toward installation of a methoxime moiety based on previous experience and on some literature precedents. 23 Accordingly, the starting acetophenone 14 was subjected to our recently developed cerium(III)-catalyzed methoximation 24 with methoxylamine hydrochloride and NaOAc in EtOH at 50 °C (Scheme 2).…”
Section: Scheme 1 Retrosynthetic Analysis Of the Target Natural Isoqumentioning
confidence: 99%
See 1 more Smart Citation
“…However, we were inclined toward installation of a methoxime moiety based on previous experience and on some literature precedents. 23 Accordingly, the starting acetophenone 14 was subjected to our recently developed cerium(III)-catalyzed methoximation 24 with methoxylamine hydrochloride and NaOAc in EtOH at 50 °C (Scheme 2).…”
Section: Scheme 1 Retrosynthetic Analysis Of the Target Natural Isoqumentioning
confidence: 99%
“…1 H NMR analysis of the product indicated that it consisted of a 90:10 mixture of E/Z geometric isomers at the olefin moiety. 24 Notably, although there are a few references concerning the allyl to propenyl isomerizations of allyl moieties located ortho to imine derivatives, 29 to our knowledge, similar procedures employing methoxime derivatives of aromatic ketones have not been disclosed before. Furthermore, in our experience, the performance of the transformation compared very favorably with analogous isomerizations performed on ortho-allyl substituted benzaldehydes and benzophenones.…”
Section: Syn Thesismentioning
confidence: 99%
“…As part of our ongoing research programme, we are interested in developing simple, efficient and eco-conscious transformations and synthetic procedures [ 25 27 ]. Therefore, in pursuit of our longstanding goals and in order to shed more light on our previous observations on the promising properties of manganese salts, herein we disclose our results regarding MnCl 2 .4H 2 O as a convenient and eco-friendly methoximation catalyst ( scheme 1 ) with a set of 22 examples of known and unknown methoximes, and compare the results with the performance of analogous methoximations at the state of the art, including those which employ CeCl 3 .7H 2 O as promoter [ 22 ]. The proposed use of MnCl 2 .4H 2 O for methoximations is novel and original, since despite its ready availability the salt has been employed rather scarcely in organic chemistry, and mostly in C–C bond-forming processes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group reported the use of oximes as synthetic intermediates for the total synthesis of natural isoquinolines [12,13]. The formation of these oximes was carried out through the use of CeCl3.7H2O as an efficient and eco-friendly promoter, as developed by Cortés et al [14]. Against this background, we have studied CeCl3-assisted hydrazonation of acetophenones and benzaldehydes in order to explore a new eco-friendly approach to this reaction (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%